2021
DOI: 10.15252/embj.2020106434
|View full text |Cite
|
Sign up to set email alerts
|

m6A‐mediated alternative splicing coupled with nonsense‐mediated mRNA decay regulates SAM synthetase homeostasis

Abstract: Alternative splicing of pre-mRNAs can regulate gene expression levels by coupling with nonsense-mediated mRNA decay (NMD). In order to elucidate a repertoire of mRNAs regulated by alternative splicing coupled with NMD (AS-NMD) in an organism, we performed long-read RNA sequencing of poly(A) + RNAs from an NMD-deficient mutant strain of Caenorhabditis elegans, and obtained full-length sequences for mRNA isoforms from 259 highconfidence AS-NMD genes. Among them are the S-adenosyl-L-methionine (SAM) synthetase (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 118 publications
0
33
0
Order By: Relevance
“…In the studies of four endocrine tumors, the expression level of METTL16 was positively correlated with overall survival. It was observed that METTL16 plays an important role in the development of endocrine system tumors, and METTL16 is a protective gene [ 20 ]. Nevertheless, several limitations should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of four endocrine tumors, the expression level of METTL16 was positively correlated with overall survival. It was observed that METTL16 plays an important role in the development of endocrine system tumors, and METTL16 is a protective gene [ 20 ]. Nevertheless, several limitations should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation at this site prevents the binding of the splicing factor U2AF65 and thereby alters the proper splicing of SAM synthetase. [113,114] While the sam pre-mRNA is not regulated in this fashion in mammals, the mechanism of splicing inhibition by 3′ss-m 6 A appears conserved. More studies are needed to decipher to which extent this mechanism participates in splicing regulation in higher eukaryotes and if an interplay with RNA editing occurs.…”
Section: Splicingmentioning
confidence: 99%
“…Presence of the m 6 A methylation can have two major consequences: they can either repel proteins that would otherwise normally bind the unmethylated sequence or enable specific binding by ''reader'' proteins that can recognize the mark (Edupuganti et al, 2017). As an example of the former situation, 3 0 splice site m 6 A is shown to repel binding of the splicing factor U2AF35, inhibiting RNA splicing (Mendel et al, 2021;Watabe et al, 2021;Yoshida et al, 2020). However, much of the biology of m 6 A is believed to be mediated by ''reader'' proteins, with the conserved YTH family of proteins being the best studied (Patil et al, 2018;Stoilov et al, 2002;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%